Exergame-Design and Motor Activities Teaching: An Overview of Scientific Paradigms on Motor Control - Di Tore, Pio Alfredo; Raiola, Gaetano (Richtmann Publishing, 2012)
This study is part of a larger project designed to assess the effectiveness of the use of exergames in the teaching ofmotor activities. The project starts with an overview of the state of the art of exergames and the influence of psychologicalmodels of the movement in software design. The experimental section of the project involves the creation of 3 exergameseducational, of which:an exergame related to visuomotor integration, on the basis of tests as Bender Gestalt and VMI, anexergame dedicated to test, in augmented / virtual environments, some commonly accepted principles in motor control (speedaccuracytrade-off, Hick's law, stimulus – response compatibility, Fitts' law), and an exergame related to the acquisition ofcognitive skills through the involvement of the whole body (reading – writing skills). In this general framework, this study locatesitself as the scientific starting basis, providing an overview of the literature on exergames (from which does not seem to bepresent exergames specifically designed for use in teaching of motor activity) and a summary of the psychological models ofmovement